Development and characterization of dissimilar aluminum welded joints via cold metal transfer technique: microstructural performance, hardness distribution, and tribological insights - Haque, Md Shakibul; Moeed, K M (Engineering Research Express, 2025)
Dissimilar aluminum welding is critical in aerospace, automotive, and transportation industries to achieve desired mechanical and structural properties. However, conventional fusion welding techniques face significant challenges in joining dissimilar aluminum alloys due to disparities in thermal expansion, solidification behavior, and wear resistance. These challenges often result in porosity, hot cracking, and reduced joint performance. Cold metal transfer (CMT) welding mitigates these issues by utilizing a low heat input, precise wire feeding, and controlled shielding gas supply, ensuring stable and efficient welds. This study investigates the CMT welding of dissimilar AA6082-T6 and AA7075-T6 sheets under varying heat inputs of 88 J mm −1 (HI1), 204 J mm −1 (HI2), and 469 J mm −1 (HI3), focusing on microstructural evolution, microhardness, and tribological characteristics. Microstructural analysis showed that increasing heat input from HI1 to HI2 reduced voids and refined grains, while further increasing it to HI3 resulted in coarser grains and evaporation of strengthening phases. XRD analysis detected α -Al, Mg2Si, Al2CuMg, and Al13Fe4 intermetallic phases in the weld metal, with reduced peak intensities at higher heat inputs, indicating deteriorated joint quality. Electron backscatter diffraction (EBSD) revealed the HI2 sample exhibited fine dendritic grains (AGS: 27.45 ± 3.10 μm) and a high-angle grain boundary (HAGB) fraction of 0.4702. Conversely, HI3 displayed coarser grains (AGS: 43.05 ± 2.03 μm) and an increased HAGB fraction (0.5302), indicating significant grain boundary transformation. Among the samples, HI1 welds exhibited the highest microhardness (94 HV) with least wear rate (0.000873 mm 3 m −1 ), highlighting the correlation between hardness and wear resistance with varying heat inputs.